2019
DOI: 10.3390/pharmaceutics11120678
|View full text |Cite
|
Sign up to set email alerts
|

Bi-Layered Polymer Carriers with Surface Modification by Electrospinning for Potential Wound Care Applications

Abstract: Polymeric wound dressings with advanced properties are highly preferred formulations to promote the tissue healing process in wound care. In this study, a combinational technique was investigated for the fabrication of bi-layered carriers from a blend of polyvinyl alcohol (PVA) and sodium alginate (SA). The bi-layered carriers were prepared by solvent casting in combination with two surface modification approaches: electrospinning or three-dimensional (3D) printing. The bi-layered carriers were characterized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 75 publications
(114 reference statements)
0
23
0
Order By: Relevance
“…Until now, different types of biopolymers were used to produce such biomaterials. Nevertheless, obtaining continuous and homogenous NFs is a problematic issue using pure protein solutions since numerous parameters affect the production process [2,4]. This can be overcome by preparing blends with other polymers, such as FDA-approved poly (lactic acid) (PLA) or poly (caprolactone) (PCL).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Until now, different types of biopolymers were used to produce such biomaterials. Nevertheless, obtaining continuous and homogenous NFs is a problematic issue using pure protein solutions since numerous parameters affect the production process [2,4]. This can be overcome by preparing blends with other polymers, such as FDA-approved poly (lactic acid) (PLA) or poly (caprolactone) (PCL).…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, various poly (saccharides) were used. Over the last few years, it has been also shown that one of the important parameters is nanomaterials characteristics is fibers alignment [4,5]. A right choice of the raw polymer, solvent, and potential enables the fabrication of a product with a designed and ordered morphology.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The bi-layered carriers presented favorable properties for dermal use with minimal tissue damage. In addition, electrospun NFs on SC films (bi-layered SC/NF carrier) provided the best physical structure for cell adhesion, and proliferation as the highest cell viability was measured compared to the SC film and the carrier with a patterned 3D printed layer (bi-layered SC/3D carrier) [1].…”
mentioning
confidence: 99%